Disease activity and functional status in Turkish patients with rheumatoid arthritis - (:unkn) unknown (My University, 2003)
Objective: Turkish patients with rheumatoid arthritis (RA) followed in a university rheumatology clinic, were evaluated cross-sectionally for clinical, socio-economical and laboratory features, correlations with disease activity (DAS) and functional outcome were assessed using a Modified Health Assessment Questionnaire (M-HAQ). Methods: Sixty-five patients with RA (F/M: 8/1, mean age: 49.7 ± 11,9 years) were investigated. Besides socio-demographic evaluations, patients were analyzed for clinical disease activity, laboratory findings and medication. Univariate and logistic regression analysis of the scores with DAS and M-HAQ were performed. Results: Despite a long disease duration (97,0+76,9 months) the functional indices (M-HAQ: 0,6±0,6 and ACR: 2,1±0,9) of the patients were limitedly elevated. However, pain visual analog scale (VAS: 3,5±2,7), tender joint score (TJS: 8,3±8,3), swollen joint score (SJS: 1,9±3,2), disease activity score (DAS: 3,3±1,3), deformed joint score (DJS: 3,2±5,6) and acute phase responses (ESR: 57,8±58,2 mm/h, CRP: 15,9±15,2 mg/dl) were moderately high in our population. DAS was found to correlate with most activity criteria, whereas M-HAQ had a limited correlation. Conclusion: Our results suggest that the average RA patient has a limited disability after a mean of 8 years of disease duration in a Turkish university clinic setting. However, disease activity was not suppressed adequately in most patients. DAS was observed to be a good composite measure of disease activity, in good correlation with most single activity measurements.
Keywords: Disease activity scores; Health Assessment Questionnaires; Rheumatoid arthritis